Muslim and Non-Muslim Perception of Social Interaction Between Religious in Malaysia - Hadana, Hadana; You, Khoo Chen (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this study was to analyze the perception of Muslim and non-Muslim communities on the relationship between interreligious social interaction in Malaysia. Plurality or diversity is inevitable, one of which is religious diversity. Malaysia is a country with a high level of religious diversity, although most of its territory is dominated by Islam. This diversity is a challenge, especially for the government to unite it especially in that there are various differences that can cause conflict. Good interaction between religions is one way to reduce inequality or differences between religions, where with good interaction can eliminate misunderstandings that might occur. So, there needs to be research related to this. This type of research is a qualitative descriptive study, with cool research namely Muslim and non-Muslim communities in Malaysia where the sampling technique used is purposive sampling. The type of data used in this study is primary data with data retrieval techniques namely observation, interviews and documentation. Based on the results of the study showed that the perception of Muslim and non-Muslim societies on the relationship of social interaction between religions in Malaysia is very good, where both Muslim and non-Muslim communities say that they can live side by side, even though in a state life non-Muslim people still accept different treatment by the Malaysian government.